Identifying the phytochemical content in Illicium verum (Star Anise) extracts prepared with different polarity solvents based on a simple maceration method - Mohd Idris, Alya Athirah; Asman, Saliza; Muhammad Hafizuddin Mohamed,; Muhammad Azizi Najmi Mamat Ali,; Wan Muhammad Faris Hadi Wan Sulaimi, (Enhanced Knowledge in Sciences and Technology, 2024)
Star anise (Illicium verum), an evergreen Chinese plant, is renowned for its rich phytochemical composition and diverse medicinal properties. This study focuses on identifying the phytochemical composition of Illicium verum extracts. The choice of solvent polarity during extraction can significantly influence the phytochemical profile and bioactivity of the resulting Illicium verum extracts. Hence, different polarity solvents were utilized, including n-hexane, distilled water, and methanol by using the maceration method. Additionally, standard phytochemical tests were conducted to elucidate the phytochemical profile further. The results revealed significant variations in the phytochemical content among the extracts obtained with different solvents. The foam test confirmed the presence of saponins, indicated by the formation of foam upon mixing with water. The alkaline reagent test demonstrated the presence of flavonoids, evident from the development of a yellow color. Furthermore, the ferric chloride test revealed the presence of tannins and phenolic compounds, as indicated by the formation of brownish-green and bluish-black colors, respectively. Specifically, methanol extract exhibited a higher concentration of phenolics, tannins, and flavonoid compounds compared to distilled water extract, while n-hexane extract showed superior content of saponins. These findings underscore the importance of solvent selection in optimizing the extraction of specific phytochemicals from Illicium verum. Overall, this study provides comprehensive insights into the phytochemical constituents of Illicium verum, essential for understanding its medicinal properties and potential applications in various industries.